Classic fairy tales : the VCD that reads with me!. (Magnavision, 2005)
3 great stories such as Beauty and the beast, Jack and the beanstalk, the tortoise and the hare
Volume 2; appropriate to ages two and above.
Keywords: Beauty and the beast; jack and beanstalk; the tortoise and the hare